Synthesis of Tungsten Carbide-Filled Multiwalled Carbon Nanotubesby DC Arc Discharge Plasma in Ambient Air; Nanotechnologies in Russia; Vol. 14, iss. 11-12 - Pak A. Ya. Aleksandr Yakovlevich (2019, 2019)
Title screen